Comprensión de la didáctica de las prácticas docentes (2012)
Teaching, as a profession, takes into account intention and actions, as well as the reconfiguration of the parts involved: teacher and students. It helps building realities in environments defined by the culture, the institutions and the society itself. Teachers develop their practice including their own distinctive features as human beings and transmit their experience with world around them. It is expected that, through their profession, teachers contribute with the process of building the society.Teaching methodologies can be studied from different perspectives: the human, the institutional, the social or the didactic perspectives.The latter is dened as a way to make and carry out the teaching-learning process, which leads to knowledge of different objects of study; this process can be broken down into stages: before starting work in the classroom, during the session and finally, the assessment of the methodology, which must be done by every teacher in order to enforce changes that may have arisen during the reflection. Also, the different teaching strategies that teachers use can be studies, as well as the reasons why those strategies were chosen